2018
DOI: 10.1080/2331205x.2018.1430652
|View full text |Cite
|
Sign up to set email alerts
|

A tele-mentoring tobacco cessation case consultation and education model for healthcare providers in community mental health centers

Abstract: Smoking prevalence among individuals with mental and behavioral health needs is considerably higher compared to the general population, but evidence-based smoking cessation therapies are underutilized in mental and behavioral healthcare settings, despite the fact that these treatments are both safe and effective. The goal of this paper is to present the background, design and pilot of Project TEACH (Tobacco Education and Cessation in the Health System) developed to improve clinical practice by offering special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…17,36,38,39,51,52,56,71 In a subset of assessments, knowledge surveys were constructed by the authors and administered. 15,23,26,39,41,47 The authors found significant improvements in objectively measured content knowledge. By contrast, a cluster randomized controlled trial on chronic pain education did not show knowledge gains among ECHO participant clinics compared with nonparticipant clinics.…”
Section: Provider-related Outcomesmentioning
confidence: 93%
See 1 more Smart Citation
“…17,36,38,39,51,52,56,71 In a subset of assessments, knowledge surveys were constructed by the authors and administered. 15,23,26,39,41,47 The authors found significant improvements in objectively measured content knowledge. By contrast, a cluster randomized controlled trial on chronic pain education did not show knowledge gains among ECHO participant clinics compared with nonparticipant clinics.…”
Section: Provider-related Outcomesmentioning
confidence: 93%
“…Change in confidence and self-efficacy focused on whether providers reported greater confidence in ability to diagnose and/or treat patients following EELM participation. 17,23,26,30,32,34,41,48,51,52,56,71 Metrics along these lines were reported in most studies, ranging from selfreported changes following participation, 32 to within-subjects change from baseline to endline, 48 to between-subjects comparisons in perceived competence, 30 including in one randomized controlled trial (RCT). 26 In most instances, results were positive and significant; a notable exception came from the RCT on chronic pain management.…”
Section: Provider-related Outcomesmentioning
confidence: 99%
“…However, not having cases from Spokes to present was a struggle to the program, which was also described in an ECHO program about tobacco cessation. 14 It is important to note the PCPs' resistance to the didactics component in the original ECHO model in the context of cancer control, which to our knowledge was not previously reported in any context. Of note, the cancerrelated ECHO programs in previous literature have a narrower focus or was a one-time training outside of the United States.…”
Section: Discussionmentioning
confidence: 64%
“…Of note, the cancerrelated ECHO programs in previous literature have a narrower focus or was a one-time training outside of the United States. [12][13][14][15] Unlike the non-PCPs, some PCPs felt they did not have a big knowledge gap in the didactics content on cancer control. They thought guidelines have a limitation on recognizing the nuances of individual health and social circumstances in their practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation